2021
DOI: 10.1038/s41586-020-03175-7
|View full text |Cite
|
Sign up to set email alerts
|

Author Correction: Transcript expression-aware annotation improves rare variant interpretation

Abstract: A Correction to this paper has been published: https://doi.org/10.1038/s41586-020-03175-7

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…This suggests that the signal is not solely driven by the most pathogenic variants nor direct rare variant effects on splicing. These results extend the previous work, comparing different exons and showing accumulation of stop-gained variants on those with lower inclusion (Cummings et al 2020). Here, observe a similar pattern when comparing different individuals within a given exon, consistent with the hypothesis that the penetrance of coding alleles is reduced when they fall on more lowly included exons.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…This suggests that the signal is not solely driven by the most pathogenic variants nor direct rare variant effects on splicing. These results extend the previous work, comparing different exons and showing accumulation of stop-gained variants on those with lower inclusion (Cummings et al 2020). Here, observe a similar pattern when comparing different individuals within a given exon, consistent with the hypothesis that the penetrance of coding alleles is reduced when they fall on more lowly included exons.…”
Section: Resultssupporting
confidence: 91%
“…Alternative splicing is responsible for the great diversity of isoform structures observed across human tissues and cell types (Keren et al 2010). With regard to coding variant interpretation, exons with lower expression have been shown to be less likely to harbor pathogenic variants, while ubiquitously included exons can be prioritized for gene disrupting rare variants (Cummings et al 2020). Autistic individuals with variants on the same exons have been shown to have remarkably similar disease phenotypes, putatively due to the variants having similar effects on gene dosage or function, a notable finding given the extreme heterogeneity of the condition (Chiang et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…7,[13][14][15] This enrichment is particularly striking in genes where true LoF variants are well-established to cause genetic disease that is not compatible with participation in common disease studies, thus not expected in population databases like gnomAD. [16][17][18] Such high error rates complicate studies leveraging pLoF variants seen in large cohorts to explore human gene function, an approach that has proven extremely valuable for the identification and validation of potential therapeutic targets. 19 While automated approaches to pLoF variant filtering remove a substantial fraction of errors, 7,18 multiple studies have demonstrated the value of deep manual curation of pLoF variants to identify evasion modes and sequencing artifacts missed by these automated tools.…”
Section: Introductionmentioning
confidence: 99%
“…UTMOST 18 modestly improves average imputation r 2 across tissues over PrediXcan by 36.8% 18 . Moreover, genes associated with Mendelian diseases are likely depleted for common cis-eQTLs 40,[51][52][53][54][55] . Future studies could potentially incorporate methods that use rare eQTLs 53 , trans-eQTLs, and epigenetic information 56 to predict gene expression.…”
Section: Discussionmentioning
confidence: 99%